Exploring the Association of Communication Satisfaction with the Oil and Natural Gas Industry and Risk Perceptions of Shale Energy Development. Issue 7 (3rd July 2019) - Theodori, Gene L.; Bello, Richard S.
Abstract: Despite the vast literature on shale energy development, surprisingly little empirical research has been conducted on the shale energy communicators, communication practices, and community outreach programs. Using data drawn from a random sample of individuals in two counties in the Eagle Ford Shale region of south Texas, we present a newly-constructed unidimensional scale that can be used to measure stakeholders' level of satisfaction with the oil and natural gas industry's communication performance. We then examine the relationship between individuals' level of communication satisfaction with the oil and gas industry and their perceptions of risk in regard to shale energy development in the Eagle Ford Shale. We find substantial support for the hypothesis that communication satisfaction with the oil and natural gas industry is negatively associated with risk perception. We conclude the paper with several suggestions for future research.